‘Digastricus’ axillary arch: A potential source of hyperabduction syndrome- Case report (Bangladesh Journal of Medical Science, 2024)
Axillary arch is an anatomical variant musculo-tendinous structure that originates from the latissimus dorsi muscle and often inserted to the pectoralis major muscle. Being musculo-tendinous, its one end is generally muscular and another end is tendinous. Here we report a variant muscular arch with its both ends muscular and were joined by an intermediate tendinous slip; thus, the name digastricus axillary arch. This variant form of axillary arch was encountered unilaterally in an elderly female cadaver and appeared to be compressing the neurovascular structures at the vicinity of axilla. Presence of axillary arch known to cause various complications such as brachial plexus compression, hyperabduction syndrome, thoracic outlet syndrome etc. The clinicians, therefore must have a prior knowledge of rare existence of axillary arch muscle before considering differential diagnosis in the patients presenting upper extremity neurovascular symptoms without demonstrable compressionsBangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 542-545